On page 165 of Chapter 13, how was the equality made from line 1 to line 2?


Namely, how $$ \prod_{j=1}^{\infty} \frac{1}{1-q^j} = \prod_{j=1}^{\infty} \frac{1}{(1-q^{2j-1})(1-q^{2j})}$$


Simply pair-off factors and use the fact that multiplication is commutative: \begin{align*} \prod_{j=1}^{\infty}\frac{1}{(1-q^{j})} & = \frac{1}{1-q}\frac{1}{1-q^2}\frac{1}{1-q^3}\frac{1}{1-q^4}\cdots\\ & = \left(\frac{1}{1-q}\frac{1}{1-q^2}\right)\left(\frac{1}{1-q^3}\frac{1}{1-q^4}\right)\cdots\\ & = \left(\frac{1}{1-q^{2}}\frac{1}{1-q}\right)\left(\frac{1}{1-q^4}\frac{1}{1-q^{3}}\right)\cdots\\ & = \prod_{j=1}^{\infty}\frac{1}{(1-q^{2j})(1-q^{2j-1})}. \end{align*}

  • $\begingroup$ Oh, I see. Thank you. $\endgroup$ – zodross Dec 17 '18 at 0:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.